Inhibitory Control and L2 Proficiency Modulate Bilingual Language Production: Evidence from Spontaneous Monologue and Dialogue Speech - Pivneva, Irina; Palmer, Caroline; Titone, Debra (Frontiers in Psychology, 2012)
Bilingual language production requires that speakers recruit inhibitory control to optimally balance the activation of more than one linguistic system when they produce speech. Moreover, the amount of inhibitory control necessary to maintain an optimal balance is likely to vary across individuals as a function of second language (L2) proficiency and inhibitory capacity, as well as the demands of a particular communicative situation. Here, we investigate how these factors relate to bilingual language production across monologue and dialogue spontaneous speech. In these tasks, forty-two English-French and French-English bilinguals produced spontaneous speech in their first language (L1) and their L2, with and without a conversational partner. Participants also completed a separate battery that assessed L2 proficiency and inhibitory capacity. The results showed that L2 vs. L1 production was generally more effortful, as was dialogue vs. monologue speech production although the clarity of what was produced was higher for dialogues vs. monologues. As well, language production effort significantly varied as a function of individual differences in L2 proficiency and inhibitory capacity. Taken together, the overall pattern of findings suggests that both increased L2 proficiency and inhibitory capacity relate to efficient language production during spontaneous monologue and dialogue speech.